2013
DOI: 10.1093/gerona/glt041
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Prevents the Progression of Sarcopenia in Aged Mice In Vivo and In Vitro

Abstract: Sarcopenia is characterized by the age-related loss of muscle mass and strength. One of the mechanisms of sarcopenia is the loss in the function and number of muscle satellite cells. Royal jelly (RJ) is a health food used worldwide. To obtain better digestion and absorption than RJ, protease-treated RJ (pRJ) has been developed. RJ and pRJ have been suggested to have potential pharmacological benefits such as prolonging the life span and reducing fatigue. Because these effects may improve sarcopenia and the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Aging-dependent declines in serum IGF-1 levels may also contribute to loss of muscle mass (Perrini et al 2010); a recent study has shown that loss of muscle mass in aged mice can be attenuated partly by increasing serum IGF-1 levels by feeding royal jelly (Niu et al 2013). Therefore, the increases in serum IGF-1 and IGF-1 receptor mRNA levels and decreases in IGFBP-5 mRNA levels after habitual exercise plus dietary MFGM might have contributed to the increase in muscle mass and contractile force production in SAMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Aging-dependent declines in serum IGF-1 levels may also contribute to loss of muscle mass (Perrini et al 2010); a recent study has shown that loss of muscle mass in aged mice can be attenuated partly by increasing serum IGF-1 levels by feeding royal jelly (Niu et al 2013). Therefore, the increases in serum IGF-1 and IGF-1 receptor mRNA levels and decreases in IGFBP-5 mRNA levels after habitual exercise plus dietary MFGM might have contributed to the increase in muscle mass and contractile force production in SAMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results show that the daily intake of RJ improves muscle strength and physical performance in elderly volunteers, as seen in mice both in vitro and in vivo (Niu et al, 2013). Yet, care should be taken since sufficient data are lacking.…”
Section: Promising Developments and Perspectivesmentioning
confidence: 98%
“…Phase III clinical trials are already underway to assess the effects of RJ on elderly people (Niu et al, 2013). Preliminary results show that the daily intake of RJ improves muscle strength and physical performance in elderly volunteers, as seen in mice both in vitro and in vivo (Niu et al, 2013).…”
Section: Promising Developments and Perspectivesmentioning
confidence: 99%
“…RJ exhibits a wide variety of functional properties, and has been widely used in cosmetics, healthy foods and commercial medical products in numerous countries. Additionally, RJ possesses various properties, including antimicrobial (2), anti-inflammatory (3,4), hepatoprotective (5), antisarcopenia (6), insulin-like action (7) and antihypercholesterolemic (8) properties. In the recent decades, there have been an increasing number of studies investigating the effects of RJ.…”
Section: Introductionmentioning
confidence: 99%